On Pre-Lie Magnus Expansion - Al-Kaabi, Mahdi Jasim Hasan (Al-Nahrain Journal of Science, 2019)
In this paper, the classical and pre-Lie Magnus expansions have been studied, discussing how one can find a recursion for the pre-Lie case which already incorporates the pre-Lie identity. A combinatorial vision of a numerical method proposed by S. Blanes, F. Casas, and J. Ros in [4], has been given on a writing of the classical Magnus expansion in a free Lie algebra, using a pre-Lie structure.